Improving Research Infrastructure in Indonesia through Public Private Partnership (PPP) - Suardi Kadang (The Journal of Indonesia Sustainable Development Planning, 2022)
The government continues to boost infrastructure development through different financing schemes, such as Public Private Partnership (PPP). The private sector is encouraged to participate in infrastructure development under this strategy, indirectly reducing the government's burden. National Research and Innovation Agency (BRIN), formerly known as the Indonesian Institute of Sciences (LIPI), as a government organization engaged in research, has chosen the PPP scheme for the Management and Development of the National Research Vessel Fleet to strengthen the capacity of the research infrastructure. This paper was written as a descriptive qualitative investigation using the literature study approach and relevant policy/regulatory literature. Also explains the need for research infrastructure, in this case, research vessels in Indonesia and provides an overview of the revenue potential and risk analysis in PPP projects. The result of this paper also provides an overview of BRIN's PPP implementation process. It can address issues such as whether the PPP scheme for research infrastructure development is of the PPP character, where the process is purely business-managed, how risk sharing is carried out in the PPP and how BRIN implements PPPs.